2006
DOI: 10.1038/sj.bjc.6603169
|View full text |Cite
|
Sign up to set email alerts
|

Efaproxiral red blood cell concentration predicts efficacy in patients with brain metastases

Abstract: Efaproxiral (Efaproxynt, RSR13), a synthetic allosteric modifier of haemoglobin (Hb), decreases Hb-oxygen (O 2 ) binding affinity and enhances oxygenation of hypoxic tumours during radiation therapy. This analysis evaluated the Phase 3, Radiation Enhancing Allosteric Compound for Hypoxic Brain Metastases; RT-009 (REACH) study efficacy results in relation to efaproxiral exposure (efaproxiral red blood cell concentration (E-RBC) and number of doses). Recursive partitioning analysis Class I or II patients with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…In addition, a clinical study has shown that acetyl-CoA metabolism is important with high level of acetyl-CoA oxidase 1 in BM from breast cancer in comparison to other metastatic sites, however differences between BM themselves was not investigated 39 . The present work, together with those previously published 24,26,27,[40][41][42][43][44][45][46][47][48][49] , highlight the importance of (i) characterizing the BM microenvironment in individual patients, and (ii) adapting external RT to the presence of hypoxia for better tumor control. Zakaria and colleagues have highlighted the importance of using more functional MRI biomarkers, such as diffusion-MRI, rather than conventional contrast-enhanced MRI for RT planning to improve BM control 50 .…”
Section: Discussionsupporting
confidence: 55%
“…In addition, a clinical study has shown that acetyl-CoA metabolism is important with high level of acetyl-CoA oxidase 1 in BM from breast cancer in comparison to other metastatic sites, however differences between BM themselves was not investigated 39 . The present work, together with those previously published 24,26,27,[40][41][42][43][44][45][46][47][48][49] , highlight the importance of (i) characterizing the BM microenvironment in individual patients, and (ii) adapting external RT to the presence of hypoxia for better tumor control. Zakaria and colleagues have highlighted the importance of using more functional MRI biomarkers, such as diffusion-MRI, rather than conventional contrast-enhanced MRI for RT planning to improve BM control 50 .…”
Section: Discussionsupporting
confidence: 55%
“…RSR-13 is a synthetic allosteric modifier of hemoglobin (Hb), which decreases Hb-oxygen binding affinity, resulting in increased tumor oxygen concentration in tumor cells (Stea et al 2006). Suh et al conducted a Phase III trial, randomizing 538 patients with brain metastases to 30 Gy WBRT with supplemental oxygen with or without RSR-13 (Suh et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…101 Due to WBRT limitations, there is increasing interest in incorporating chemical modifiers with WBRT. Motexafin-gadolinium, 102 efaproxaril, 103 and temozolomide 104,105 are among the many agents that are currently being investigated.…”
Section: Discussionmentioning
confidence: 99%